Toxicidade de lixiviado de aterro controlado em Eisenia andrei (Bouché, 1972) (Oligochaeta), em substrato artificial tropical - Pontes, Aristófanes Romão da Cunha (2013)
On a global level, the generation and direction of municipal solid waste is a worrying situation. In Morretes – PR, 14 tons of solid waste are generated daily and require proper management, however, of this total over 6 tons are improperly disposed of in the sole landfill existing in the municipality of Morretes. The leachate generated is characterized as a highly toxic substance and requires proper treatment to prevent pollutants from contaminating groundwater, surface water and soils, causing negative effects on their biota. Ecotoxicology arises to study the effects of these substances at different levels of biological ecosystems. Ecotoxicological behavior (leakage) and acute and chronic toxicity (mortality and reproduction) using Artificial Tropical Substratum (AST) were performed in order to evaluate the toxicity of leachate from the Morretes landfill in Eisenia andrei (Oligochaeta). The leachate was collected in two phases, the first in July and the second in September 2012. Six treatments were utilized (0%, 20%, 40%, 60% 80% and 100%) corresponding to the concentrations of leachate with four replicates each and 10 individuals of adult Eisenia andrei were used with biomass between 200 mg - 550 mg. The pH of the AST measured in the water was 6.3. For the leakage test, plastic containers were used with a transverse division in which 250g AST was placed in each side corresponding to the control and treatment. To test toxicity, plastic containers with a capacity of 700 ml were used, in which 500g AST were placed with different treatments. Greater leakage was observed at concentrations of 80% and 100% of the first leachate collection and no leakage i.e. attraction of organisms in the leachate from the second collection. The mortalities of two individuals in concentrations of 20% and 40% of the leachate from the second collection were found, representing only 2.5% mortality, whereas no mortality in the first leachate collection was observed. In the chronic test (reproduction) less than 30 individuals per unit were born in the control treatment. There was biomass loss in the three tests, though not statistically significant and not presenting a doseresponse relationship. It was not possible to estimate the median lethal concentration or the average concentration effective for not registering mortality during the 56 days of experiment. These results contradict the hypothesis that the leachate brought about negative effects (mortality and leakage) in Eisenia andrei individuals in that the concentration of the leachate increase and might indicate that the seasonality and the treatment process by recirculation that the leaching through that the Morretes landfill has been experiencing for the last two years, may be decreasing the presence of heavy metals and other pollutants in the leachate.